Understanding the effects of mild traumatic brain injury on the pupillary light reflex - Kenneth J Ciuffreda; Nabin R Joshi; James Q Truong (Concussion)
The pupillary light reflex represents an optimal visual system to investigate and exploit in the mild traumatic brain injury (mTBI) population. Static and dynamic aspects of the pupillary light ref...